DESIGN OF ROBUST TWO-AXIS SYSTEMS FOR STABILIZATION AND TRACKING OF INFORMATION-MEASURING DEVICES OPERATED ON GROUND VEHICLES - Sushchenko, Olga (Proceedings of National Aviation University (archive), 2014)
Design features of the information-measuring robust stabilization and tracking systems operated on the ground vehicles are considered. The mathematical description of the control object mounted in the two-axis gimbals is obtained. Design features of the two-axis robust stabilization and tracking systems based on the structural H.. -synthesis are researched. The simulation results are given